2016
DOI: 10.1111/1440-1630.12337
|View full text |Cite
|
Sign up to set email alerts
|

Practice education: A snapshot from Australian university programmes

Abstract: Practice education is a critical issue for Australian occupational therapy. Increasing student numbers place mounting financial and resource demands on education programmes and practice education providers. There is a need for a national, collaborative approach to develop guidelines and processes to ensure sustainability relating to practice education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…[18][19][20] Because there is a reported rising scarcity of clinical placements in healthcare, any growth and commitment to educating future professionals is commendable. 2,3,10 Customised survey response data As shown in Fig. 2 nine overarching themes emerged from the thematic review of survey response data.…”
Section: Trending Placement Allied Health Staff University Program mentioning
confidence: 99%
See 2 more Smart Citations
“…[18][19][20] Because there is a reported rising scarcity of clinical placements in healthcare, any growth and commitment to educating future professionals is commendable. 2,3,10 Customised survey response data As shown in Fig. 2 nine overarching themes emerged from the thematic review of survey response data.…”
Section: Trending Placement Allied Health Staff University Program mentioning
confidence: 99%
“…Therefore, the demand for allied health clinical placements will continue to increase due to growth in university health programs and cohort numbers. 2,3 The capacity of public health services to support placement demand has been a topic of discussion within services and across stakeholder groups responsible for the professional learning of pre-entry students. 2,[4][5][6] It is well recognised that commitments to clinical education at a national and state government level, innovation in clinical placement provision and support and recognition for clinical educators all contribute to the capacity of health services to meet increasing placement demand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PASS for Placement provides opportunities for occupational therapy students in all year levels to develop their preparedness for practice education, supplementing core and existing teaching activities. It is not designed to address increasing staff-student ratios, or is it specifically for 'at risk' students (Gustafsson et al, 2016;Hammond et al, 2010). Unlike PASS programmes previously reported by other health disciplines (Hammond et al;Ross & Cameron, 2007;Secomb, 2008;Sole et al, 2012;Williams et al, 2014), PASS for Placement is not subject specific.…”
Section: Pass For Placementmentioning
confidence: 99%
“…Dawson, van der Meer, Skalicky and Cowley (2014) reported there was a need for "interventions to support greater bodies of more diverse students at financially constrained tertiary institutions" (p. 612). A number of authors have identified the value of peer learning (Gustafsson et al, 2016;Martin & Edwards, 1998;Price & Whiteside, 2016;Sevenhuysen, Nickson, Farlie, Raitman & Keating, 2013;Tai, Haines, Canny & Molloy, 2014) and this study explores whether peer assisted learning models can be applied to preparing students for practice education.…”
Section: Introductionmentioning
confidence: 99%